2020
DOI: 10.2147/cmar.s246166
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA DLGAP1-AS1 Promotes the Aggressive Behavior of Gastric Cancer by Acting as a ceRNA for microRNA-628-5p and Raising Astrocyte Elevated Gene 1 Expression</p>

Abstract: Purpose: The long noncoding RNA DLGAP1 antisense RNA 1 (DLGAP1-AS1) plays welldefined roles in the malignant progression of hepatocellular carcinoma. The purpose of this study was to determine whether DLGAP1-AS1 affects the aggressive behavior of gastric cancer (GC). Methods: DLGAP1-AS1 expression in GC tissue samples and cell lines was determined by reverse-transcription quantitative PCR. GC cell proliferation, apoptosis, migration, invasion, and tumor growth in vitro as well as in vivo were examined by the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The present work proved that DLGAP1-AS1 was an oncogenic lncRNA in GC, which indicated it could be a promising biomarker and therapy target. Interestingly, our results are in agreement with a recent study that reported that the increased expression of DLGAP1-AS1 in GC tissues correlates with tumor size, TNM stage, lymph node metastasis, distant metastasis, and poor prognosis of the patients (19). lncRNA acts as a competitive endogenous RNA (ceRNA), so-called molecular sponge, to interact with miRNA and inhibit miRNA expression to reduce the miRNA repressive effect on targeting mRNA (20).…”
Section: Discussionsupporting
confidence: 93%
“…The present work proved that DLGAP1-AS1 was an oncogenic lncRNA in GC, which indicated it could be a promising biomarker and therapy target. Interestingly, our results are in agreement with a recent study that reported that the increased expression of DLGAP1-AS1 in GC tissues correlates with tumor size, TNM stage, lymph node metastasis, distant metastasis, and poor prognosis of the patients (19). lncRNA acts as a competitive endogenous RNA (ceRNA), so-called molecular sponge, to interact with miRNA and inhibit miRNA expression to reduce the miRNA repressive effect on targeting mRNA (20).…”
Section: Discussionsupporting
confidence: 93%
“…Li et al [ 38 ] noted that IGF2-AS enhanced GC cell invasion, growth and migration by regulating miR-937/EZH2. Deng et al [ 39 ] showed that DLGAP1-AS1 induced GC progression by sponging miR-628-5p/AEG-1. Liu et al [ 40 ] noted that SNHG1 induced GC cell EMT progression via modulation of the DCLK1/miR-15b/Notch1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al. 25 reported that DLGAP1-AS1 promotes the aggressive behavior of gastric cancer by acting as a ceRNA for miRNA-628-5p and raising astrocyte-elevated gene 1 expression. Functional analyses showed that proliferation and invasion potency were decreased while apoptosis rate was increased in HT-29 and SW480 cells after DLGAP1-AS1 expression was silenced.…”
Section: Discussionmentioning
confidence: 99%